ANALISIS PERUBAHAN ASET DAN LIABILITAS PAJAK TANGGUHAN UNTUK MENDETEKSI MANAJEMEN LABA - Stepanus Kuncoro, 08.05.52.0197; Indarti, MG. Kentris (Students Journal of Accounting and Banking, 2012)
This research is a testing that examined the effect and analyze the changes in net deferred tax liabilities and changes in net deferred tax liability components related to the accrual and revenue and expenses and reserves, compensation, depreciation, valuation of fixed assets and other items of earnings management to avoid earnings decline in manufacturing companies that go public in Indonesia.The population in this research is a company engaged in the manufacturing sector are listed in Indonesia Stock Exchange (BEI) in 2008-2010. Sampling technique using a purposive sampling technique with the following criteria. According to established criteria contained 37 samples. Analysis technique used is logistic regression.The results showed that the change in net deferred tax liability have an effect positive and significant can be used to detect earnings management to avoid earnings decreases. Meanwhile, changes components of net deferred tax liability related to the accrual and revenue and expenses and reserves, compensation, depreciation, valuation of fixed assets and other items and also valuation allowance for deferred tax assets can not be used for detecting earnings management to avoid earnings decreases.Keywords: Earnings Management, Accrual, Cash Flow Operating, Size, Net Deferred Tax Liabilities, Deferred Tax Liabilities, Deferred Tax Assets.Â